Evidence of association between epstein barr virus serum antibodies with HAs and RI as biomarkers of active rheumatoid arthritis - Perez, Germán (2018)
Background: Epstein Barr Virus (EBV) infection has been associated with the Rheumatoid Arthritis (RA) etiopathology, thus, considering it a relevant etiological agent in the disease development. We have previously observed the Hyaluronic Acid (HA) serum increase in active RA patients (DAS 28-4 > 2.6) which might be responsible for the erythrocyte deformability, estimated by the erythrocyte Rigidity Index (RI). Objective: In the present study, we analyzed in one hundred RA patients if anti-EBV serum antibodies (TsEBV) and HA and RI levels are related with the disease activity. Results: [HA] s [[controls]]: 20.0 ± 9; [HA] s [[AR]]: 155.8 ± 44 (p< 0.00001 vs. controls (n:40). Antibodies anti-EBV (1/ TsEBV) [[controls]]: 2.55 ± 0.49; [[RA]]: 1.85 ± 0.35 (p< 0.00001 vs. controls). There were significant correlations between DAS 28-4 vs. log2 1/TsEBV (r: 0.70, p < 0.00001) and DAS 28-4 vs. RI (r: 0.75, p < 0.00001) in active RA patients. However, we observed a strong positive correlation between [HA] s in active RA patients vs. log2 1/TsEBV (r: 0.83, p < 0.00001) and [HA] s vs. RI (r: 0.91, p < 0.00001). Conclusion: The correlation obtained points out that the TsEBV may be related with the degree of RA activity determined by DAS28-4 and [HA]s in these patients. There was also a decrease in erythrocyte deformability estimated as RI, which is correlated with the DAS 28-4 activity index. Therefore, RI can be used as a reliable marker of RA activity. These findings might suggest a role of EBV infection regarding an autoimmune mechanism present in RA.